2011
DOI: 10.19030/jber.v3i1.2731
|View full text |Cite
|
Sign up to set email alerts
|

Student Performance In Upper-Division Business Core Courses: Using Control Variables To Determine The Effect Of Class Size

Abstract: <p class="MsoBlockText" style="text-indent: 0in; margin: 0in 27pt 0pt; mso-pagination: none;"><span style="font-style: normal; mso-bidi-font-style: italic;"><span style="font-size: x-small;"><span style="font-family: Times New Roman;">Although the effect of class size upon student performance has been the focus of numerous studies, the results have been extremely mixed, including positive effects, no effects, and negative effects.<span style="mso-spacerun: yes;">&nbsp; </sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Maasoumi et al (2005) discovered class size had a non-uniform impact on ratings. Driscoll et al (2005) report studies with widely differing conclusions: some indicate class size has a positive impact, some a negative impact, and some indicate no correlation at all. Centra and Gaubatz (2000) found that class size affects evaluations only when the class size is under 15 students.…”
Section: Introductionmentioning
confidence: 99%
“…Maasoumi et al (2005) discovered class size had a non-uniform impact on ratings. Driscoll et al (2005) report studies with widely differing conclusions: some indicate class size has a positive impact, some a negative impact, and some indicate no correlation at all. Centra and Gaubatz (2000) found that class size affects evaluations only when the class size is under 15 students.…”
Section: Introductionmentioning
confidence: 99%